Evaluation of safety and effectiveness of remdesivir in treating COVID-19 patients after emergency use authorization study - Burhan, Erlina; Syahruddin, Elisna; Isbaniah, Fathiyah; Desianti, Ginanjar Arum; Fachrucha, Fanny; Sari, Cut Yulia Indah; Ismail, Efriadi; Astuti, Puji; Maruli, Muhammad Farhan; Mubarak, Farhan; Rengganis, Anggit Tresna; Bilqis, Hazia Hanifa; et al. (Frontiers in Pharmacology, 2023)
Background: This study aimed to determine the real-world safety and effectiveness of remdesivir in hospitalized adult COVID-19 patients with moderate-to-critical disease in Indonesia. Methods: A multicenter, retrospective cohort study was conducted at four COVID-19 referral hospitals in Jakarta. A total of 587 patients were included, of whom 243 received remdesivir within 72 hours of admission. The safety endpoints were the proportions of patients with any adverse event (AE), any grade 3 AE, and AE of each system organ class. The effectiveness endpoints were ICU admission >24 hours from baseline, live discharge and mortality at day 14, live discharge and mortality at day 28, and virologic conversion. Patients who received remdesivir within 72 hours of admission were considered the treatment group, and those who did not were the control group. Multivariate adjustments were performed using a modified Poisson regression. Results: The study found no significant differences in safety endpoints between the two groups. However, the effectiveness endpoints showed that remdesivir was associated with a decreased risk of ICU admission >24 hours from baseline (RR 0.71, 95% CI 0.52–0.96), an increased probability of live discharge at day 14 (RR 1.37, 95% CI 1.08–1.74), and an increased probability of live discharge at day 28 (RR 1.28, 95% CI 1.05–1.57). The rate of virologic conversion was not significantly different between the two groups. Conclusion: The study concludes that remdesivir is safe and effective in the treatment of moderate-to-critical COVID-19 in a real-world setting in Indonesia.